The electrocardiographic 'triangular QRS-ST-T waveform' pattern: a marker of severe haemodynamic compromise in Takotsubo syndrome—a case report. Issue 3 (25th April 2020) - Joki, Tuukka; Nikus, Kjell; Laukkanen, Jari
Abstract: Background: Takotsubo cardiomyopathy is characterized by transient regional systolic dysfunction of the left ventricle, mimicking myocardial infarction. Although systolic left ventricular (LV) function normalizes in most cases, the outcome is not always favourable. Recently, a rare electrocardiogram (ECG) finding, lambda wave ST elevation or 'triangular QRS-ST-T waveform', was suggested as a possible marker of poor outcome in Takotsubo patients Case summary: After a brief episode of chest pain and shortness of breath, a 67-year-old woman developed cardiogenic shock. Her resting ECG showed widespread ST elevations, which soon evolved into a pattern of triangular QRS-ST-T waveforms in the inferior leads and V3–V6. Emergent coronary angiography was normal. The ejection fraction was 20% with apical ballooning and an LV thrombus. At 1-month follow-up, the patient was asymptomatic and the ECG showed only T-wave inversions. Discussion: The triangular QRS-ST-T waveform ECG pattern has recently been introduced as a high-risk marker in the Takotsubo syndrome.